Relational Agency as a Dialectic of Belonging and Not Belonging within the Social Ecology of Plantation Life in Sri Lanka - Cunliffe Ann L.; Karunanayake Geetha (Journal of Organizational Sociology)
We argue that lived spaces play a crucial role in influencing how people can or cannot enact their agency. Based on an interpretive ethnographic study of work in a large Sri Lankan tea plantation and drawing on the conceptual lenses of relational agency and social ecology, we explore how workers experience their ability to act agentically in relation to their social circumstances and examine the personal and social consequences. In doing so, we extend conceptualizations of relational agency as a dialectic of belonging and not belonging within a social ecology – an ongoing flow of intertwined activities and ways of being and relating to each other that create and reproduce social orders and forms of accountability.